Recirculation Hatchery Systems and Management - Valenti, Wagner C. [UNESP]; Daniels, William H. (Wiley, 2007)
Conventional hatchery systems have been described in Chapter 5. This chapter deals with recirculation hatchery systems, which have been developed to minimise water losses and maximise water quality for raising larvae. Minimal water usage is very important for inland hatcheries, where water must be transported long distances or artificial seawater is used. Recirculation allows continuous or semi-continuous processing of water to remove nitrogen and solid wastes and disinfection for disease management. The use of recirculation systems in Macrobrachium rosenbergii hatcheries has several advantages over open systems. These include more stable water quality; lower water consumption; heat conservation; lower labour requirements; control or prevention of pollutants, parasites, predators and competitors; and enhanced feasibility of establishing inland hatcheries (Smith et al. 1976; Cohen & Ra'anan 1989; Griessinger et al. 1989).
Keywords: Hatchery design; Mechanical filters; Recirculation hatchery systems; Static closed system; Tank designs